Levantamento do gerenciamento do resíduo de madeira utilizada para a confecção de fôrmas de estrutura de concreto armado - Mossmann, Arlete Simone (Universidade do Vale do Rio dos Sinos, 2011)
The environmental concern and the interest of the construction industry in complying with the legislation arouses the research to find solutions to problems regarding the generation of construction waste. A waste management system requires a behavior change in companies and should include practices that seek to prevent and reduce the amount of waste generated, its proper disposal, reuse and recycle. This work is focused on the wood waste generated due to the manufacture of molds for concrete structure and aims to present a survey on how this waste is managed. As a research strategy, it was mainly based on the study of cases with multiple sources of evidence, involving research with construction companies, raw material suppliers, carries and receivers of this waste. The work was performed in two steps involving: a diagnosis of how construction companies in Novo Hamburgo/RS manage wood waste and a survey about computer programs used by the furniture sector aiming to adapt it to the construction sector in order to rationalize the use of wood and reduce waste generation. As a result, the study highlights the difficulties faced by construction companies to manage wood waste. Practices to rationalize the use and to recycle the material were not identified and serious problems regarding the final destination of waste were diagnosed. Alternatively, this paper shows the results on raw material savings from the use of computer program on a cutting plan.
Keywords: Construção civil; Resíduos de madeira; Racionalização; Gerenciamento de resíduos; Civil construction; Wood waste; Rationalization; Waste management; ACCNPQ::Engenharias::Engenharia Civil